2016
DOI: 10.1155/2016/2454989
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism in Pancreatic Cancer: Role of Exogenous Thyroid Hormone in Tumor Invasion—Preliminary Observations

Abstract: According to the epidemiological studies, about 4.4% of American general elderly population has a pronounced hypothyroidism and relies on thyroid hormone supplements daily. The prevalence of hypothyroidism in our patients with pancreatic cancer was much higher, 14.1%. A retrospective analysis was performed on patients who underwent pancreaticoduodenectomy (Whipple procedure) or distal pancreatectomy and splenectomy (DPS) at Thomas Jefferson University Hospital, Philadelphia, from 2005 to 2012. The diagnosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Furthermore, T3 attenuated the activity of cyclin-CDK complexes, which resulted in reduced pRb phosphorylation and G1 cell cycle arrest. In contrast, the proliferation, migration, and invasion of pancreatic cancer cells was stimulated by T3 in vitro (62). These results fit observations of patients in which hypothyroidism treated with TH supplementation correlated with increased risk of tumor progression and poor prognosis (62).…”
Section: In Vitro Studies Of the Thyroid-cancer Associationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, T3 attenuated the activity of cyclin-CDK complexes, which resulted in reduced pRb phosphorylation and G1 cell cycle arrest. In contrast, the proliferation, migration, and invasion of pancreatic cancer cells was stimulated by T3 in vitro (62). These results fit observations of patients in which hypothyroidism treated with TH supplementation correlated with increased risk of tumor progression and poor prognosis (62).…”
Section: In Vitro Studies Of the Thyroid-cancer Associationmentioning
confidence: 99%
“…In contrast, the proliferation, migration, and invasion of pancreatic cancer cells was stimulated by T3 in vitro (62). These results fit observations of patients in which hypothyroidism treated with TH supplementation correlated with increased risk of tumor progression and poor prognosis (62). Thyroid hormones were shown to potentiate cytotoxic effects of chemotherapeutics in pancreatic cancer cells (63).…”
Section: In Vitro Studies Of the Thyroid-cancer Associationmentioning
confidence: 99%
“…When a specific blocker for α V β 3 is used, reduced PANC-1 tumor mass in a mouse xenograft model, increased proapoptotic BcLx-s expression, reduced tumor hemoglobin content (a marker of angiogenesis), and decreased expression of epidermal growth factor receptor (EGFR) could be observed [ 113 ]. A recent study [ 114 ] showed that although the prevalence of hypothyroidism in patients with pancreatic cancer was 14.1%, exogenous thyroid hormone treatment in pancreatic cancer cell lines also significantly increased cell proliferation, migration, and invasion, suggesting that exogenous thyroid hormone may contribute to the progression of pancreatic cancer. On the other hand, the tumor-suppressive and antiangiogenic effects of THs were also reported.…”
Section: Thyroid Hormone and Pancreatic Cancermentioning
confidence: 99%
“…Among the top five genes identified from the interaction tests (Table 4), Lysine‐specific demethylase 3A ( KDM3A ) had a p < .01 in the replication data set. The only set of weights available for KDM3A was derived from the thyroid, a tissue found to be relevant with pancreatic cancer (Gullo et al, 1991; Sarosiek et al, 2016). This gene would be missed by using the aGE test ( p > .05).…”
Section: Resultsmentioning
confidence: 99%